2021
DOI: 10.1007/s10113-020-01728-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the provisioning of ecosystem services in South Korea under climate change: The benefits and pitfalls of current forest management strategies

Abstract: We present a study about the integrated impact of adaptive management and climate change using spatially-explicit tools at first time for assessing changes in forest ecosystem services in South Korea. The aims of this study were to: (i) project potential changes among forest ecosystem services under various scenarios, (ii) assess the impact of forest management [Sc1: controlled, Sc2: business as usual, and Sc3: adaptive management] and climate change through comparison among them, and (iii) find insight for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The KO-G-Dynamic model has previously helped enhance the forest growth model [ 37 40 ]. It can accurately predict the growth of temperate forests (which grow yearly), also considering the climatic impacts overlooked by traditional dynamic growth models [ 28 , 41 ]. These climate factors affect diameter at breast height (DBH) and mortality [ 39 , 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The KO-G-Dynamic model has previously helped enhance the forest growth model [ 37 40 ]. It can accurately predict the growth of temperate forests (which grow yearly), also considering the climatic impacts overlooked by traditional dynamic growth models [ 28 , 41 ]. These climate factors affect diameter at breast height (DBH) and mortality [ 39 , 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis reflects the current transition in the forest physiognomy in Republic of Korea from young-matured stands to over-mature forests. Four scenarios were established individually according to the application of the variables which are climate change and forest management intensity in South Korea [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment efforts use indicators that reflect biophysical and hydrological processes and changes in the temporal and spatial distribution of watershed conditions (He et al, 2000 ); AM approaches must also include socio-economic indicators that measure the dynamic interactions between environmental and social systems (Morton & Padgitt, 2005 ). For example, Kim et al ( 2021 ) explored the benefits and pitfalls of management strategies in the forests of South Korea, finding important tradeoffs between recreational uses and carbon sequestration, and between freshwater supply and wood production. Similarly, El Mahrad et al ( 2020 ) studied the socio-environmental interactions derived from the management of coastal lagoons in Northern Africa; they found that science-based knowledge is critical to informed decision-making that can result in sustainable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Kim et al (2010) conducted an important study to comprehensively evaluate the public value of forests and convert them into monetary values using alternative cost method. Similarly, Kim et al (2021b) and Lee et al (2018 quantified the dynamics of several ecosystem services over time and forest management. Although these studies supported forest management policies by focusing on the forest ecosystem services, they did not lead to land policy supporting through comparison with other land use values.…”
Section: Introductionmentioning
confidence: 99%